Portugal : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Portugal. (IMF Staff Country Reports; Country Report ;, 2022)
After a deeper pandemic-induced recession than the rest of the euro area in 2020, the Portuguese economy gained ground in 2021, and growth strengthened further in 2022:Q1. Employment reached pre-pandemic levels in 2021:H2 and GDP in 2022:Q1. Nonetheless output is expected to remain below pre-pandemic trend over the medium term. While growth in 2022:Q1 was supported by a strong bounce back in tourism and domestic demand, the recovery for the rest of the year is expected to be hampered by the war in Ukraine despite limited direct linkages with Russia and Ukraine, due to higher commodity prices, supply-side disruptions, and weaker confidence and external demand. The outlook is clouded by uncertainty relating to the war, new virus waves, and the ultimate effect of the pandemic on corporate, bank, and public sector balance sheets. While declining and with improved composition, public debt would remain high.